PELATIHAN DIGITAL MARKETING STRATEGY UNTUK MENCAPAI KEMANDIRIAN MASYARAKAT - Ayu Maulinda Wiediawati; Anggi Aprilia Pratiwi; Galang Bimandra (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
In Gunungsari Village, there is an awful lot of unemployed who need jobs to fullfill the cost of daily living. Unemployment was dominated by teenagers graduate from SMP and SMA with limited skill. The potential things that can be found in the village of Gunungsari, that was the number of Roses has been wasted when the harvest due to no consumer that takes it. This can be used as a source of potential income for unemployment by means of producing the rose water drink. Training to utilize the rose as a drink has been done to increase the skill of unemployment. To market products that have been produced, given the devotion with partners of training Digital Marketing Strategy (DMS). The results of training namely creation of perpetrators of rose water beverage production partners who divided his responsibilities to become producers, marketing, accounting and finance. The partners also had 4 accounts online shop as a result of the training of DMS. The partners also had a draft financial bookkeeping production. Training of DMS, through the manufacture of drinks rose water was able to add skill partners i.e. skill production, computing, and marketing. In addition, partners are able to follow the development of the technology through the operation of the online shop. The partners have also been able to obtain income from the proceeds of the production that resulted in a partner referred to as society.